The Impact of Knowledge Transfer on Investment in Knowledge Creation in Firms†‡ - Tafkov, Ivo; Towry, Kristy; Zhou, Flora Hailan (Contemporary Accounting Research, 2022)
ABSTRACT Knowledge is key to success in the modern business landscape. Firms invest billions of dollars every year in knowledge management systems, which commonly use artificial intelligence to allow within‐firm knowledge transfer to occur automatically. Despite this investment, these systems often fall short of producing expected results. Using psychology theory on goal dilution, we argue that a potential cause of the failure is that the prospect of knowledge transfer has a negative effect on knowledge creation. We further propose a mechanism to mitigate that effect. Specifically, we predict that the negative effect of knowledge transfer on knowledge creation will be mitigated when the linkages among firm‐ and unit‐level goals are communicated. We conduct an experiment and find that while, as predicted, the prospect of knowledge transfer has a negative effect on knowledge creation when the linkages among firm‐ and unit‐level goals are not communicated, it has the predicted positive effect when the linkages among firm‐ and unit‐level goals are communicated due to increased goal congruence. Additional analyses provide support for our underlying theories. Our results suggest that firms can adopt and communicate strategic performance measurement systems to improve the knowledge creation in a firm.